2021
DOI: 10.51630/ijes.v2i1.11
|View full text |Cite
|
Sign up to set email alerts
|

History of Utilization of the Computational Fluid Dynamics Method for Study Pico Hydro Type Cross-Flow

Abstract: Energy crisis in particular, electricity in the isolated rural areas of Indonesia is a very crucial issue that needs to be resolve through  electrification . Compared to other options, pico hydro cross-flow turbine (CFT) is the better option to provides electrical power for the isolated rural areas. Studies to improve CFT performance can be undertaken analytically, numerically, experimentally, or a combination of those methods. However, the development of computer technology makes numerical simulation studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…( 1), the nozzle inlet ratio for 𝜆 = 𝜋 2 ⁄ estimated at 0.2942, while the 𝑑 𝐶 value in this study varies from 0.0625 to 0.3125 with a 0.0625 increment. The prior study found that the water's velocity distribution approaching the turbine affects the turbine's performance [16]. On the other hand, the OCF velocity distribution is different from the in-nozzle velocity distribution and the inviscid approach.…”
Section: Cfd Simulations Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…( 1), the nozzle inlet ratio for 𝜆 = 𝜋 2 ⁄ estimated at 0.2942, while the 𝑑 𝐶 value in this study varies from 0.0625 to 0.3125 with a 0.0625 increment. The prior study found that the water's velocity distribution approaching the turbine affects the turbine's performance [16]. On the other hand, the OCF velocity distribution is different from the in-nozzle velocity distribution and the inviscid approach.…”
Section: Cfd Simulations Casesmentioning
confidence: 99%
“…However, based on two prior studies, the no-hydraulic-jump assumption was not valid, especially at higher rotational speeds. The hydraulic jump was formed due to the centrifugal force effects found in CFT since 1960 [15]. In a nozzle-equipped CFT, the centrifugal force effect generates the nozzle velocity coefficient investigated in a prior study and is valued between 0.9 and 1 [14].…”
Section: Cfd Simulations Casesmentioning
confidence: 99%
“…1 Iss. 1 July 2023, pp: 10-19 turbines [11]. That means CFT uses more water discharge and needs a lower hydraulic head than other impulse turbines [12].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, carrying out studies to optimize the geometry of these turbines is of utmost importance to achieve greater efficiency and, therefore, a higher performance in the energy production process. In the field related to turbine simulation, it is possible to identify in the literature that in turbo-machinery, the six degrees of freedom (6-DoF) user-defined function (UDF) method has been commonly used to analyze systems as cross-flow turbines [8,9,10,11], water wheel turbines [12] and open flume turbines [13]. The 6-DoF approach has not been thoroughly investigated in hydrokinetic turbine rotor modeling.…”
Section: Introductionmentioning
confidence: 99%